Sudahkah Para Akademisi Mengimplementasikan SNI 19-4192-2002 dalam Penulisan Abstrak? Studi Kasus pada Pertemuan Ilmiah Nasional Duconomics Sci-meet 2021 - Nicky Rosadi (INTELEKTIUM, 2021)
This study aims to determine whether academics have implemented SNI 19-4192-2002 in writing abstracts. The method used in this research is descriptive analysis method. The object of this research is the abstract submitted by academics who are presenters at the national scientific meeting of Duconomics Sci-meet 2021 with a total of 48 abstracts. The result of this research is that 60% of abstracts have not implemented SNI 19-4192-2002 on Documentation — Abstracts for documentation and publication. In the SNI document, it is explained that the abstract contains at least the objectives, methodology, results, and conclusions. Abstracts are presented in a concise form, which is between 100 to 250 words, and are easy to understand. Abstracts are also written in one paragraph. Then, the abstract is presented in Indonesian, and it is also advisable to prepare an abstract in English. Only 27% of academics have implemented SNI 19-4192-2002 in their abstract writing. Unfortunately, there are still 13% academics whose abstracts do not implement SNI 19-4192-2002. Based on these findings, it can be concluded that education related to abstract writing with national standards is necessary to improve the quality of scientific writing in Indonesia.